Internodular functional connectivity in heterotopia‐related epilepsy. Issue 6 (3rd May 2019) - Khoo, Hui Ming; von Ellenrieder, Nicolás; Zazubovits, Natalja; Hall, Jeffery A.; Dubeau, François; Gotman, Jean
Abstract: Objective: A vast network involving the nodules and overlying cortices is believed to be responsible for the epileptogenicity in gray matter heterotopia with multiple nodules, which often associated with difficult‐to‐treat epilepsy. We sought to determine if functional magnetic resonance imaging (fMRI) could detect internodular functional connectivity (FC), and if this connectivity reflects an actual synchronized neuronal activity and partakes in epileptogenicity. Methods: We studied 16 epilepsy patients with multiple heterotopic nodules; eight underwent subsequent intracerebral EEG. We examined the internodular FC using fMRI and its correspondence with internodular synchrony of intracerebral interictal activity. We then compared the spreading speed of ictal activity between connected and unconnected nodules; and the FC among possible combinations of nodule pairs in terms of their involvement at seizure onset. Results: Seventy nodules were studied: 83% have significant connection to at least one other nodule. Among the 49 pairs studied with intracerebral EEG, (1) synchronized interictal activity is more prevalent in fMRI‐connected pairs ( P  < 0.05), (2) ictal activity spreads faster between connected pairs ( P  < 0.0001), and (3) stronger FC was observed between pairs in which both nodules were involved at seizure onset ( P  < 0.01). Interpretation: fMRI could reliably and noninvasively detect the FC between heterotopic nodules. These functional connections correspond to the synchrony of interictal epileptic activity between the nodules and to the ability of nodules to generate synchronous seizure onsets or rapid seizure spread. These findings may help in understanding the complexity of the epileptogenic network in multiple heterotopic nodules and better targeting the likely epileptogenic nodules.